Palais de justice et prisons départementales de Pau (1850-1865) - Cécile Devos (In Situ)
Ancient capital of a kingdom, which has become the chief town of a department, Pau experienced one of the turning points in its history in the second half of the 19th century, thanks to its new reputation as a tourist and climatic resort. Its geographic and demographic expansion is supervised and relayed as it should be by the various authorities exercised on its territory. It was in particular during the Second Empire that the city was to be embellished with various buildings capable of hosting and embodying the various administrations established in the city.The Basses-Pyrénées department seized the resources at its disposal to program a wave of construction of public buildings (new courthouses, prisons and asylum, three buildings built between 1850 and 1868). At the time, the city was an ideal centre for reflection on administration buildings architecture and the departmental architects played a significant role in the urban transformations implemented. It is therefore necessary to question the place of judicial architecture in the tight network of public buildings intended to support the growth of the territory of Pau and the Basses-Pyrénées, which would seem inclined to follow national trends by adapting to their modest means. These examples have kept their original functions until today; the enhancement of this heritage is all the more interesting and useful for a better understanding of Pau’s urban history.